You are on page 1of 6

# Mathematical Induction

## PROOF BY MATHEMATICAL INDUCTION Stephen Schoupp Western Governors University

Mathematical Induction Proof by Mathematical Induction A significant facet of mathematics is to detect and differentiate reoccurring designs or sequences. To define these designs or sequences,

mathematicians implement the theorem of mathematical induction. Defined as a method of proving statements concerning a positive integral variable (Answers.com, 2008), induction seeks to establish the validity of any infinite sequence defined by a subset of natural numbers. Induction establishes the cogency of the sequences first affirmation, known as the base step, by establishing the validity of the sequence for x = 1. The next operation, the induction hypothesis, demonstrates the verity of a stochastic succeeding statement such that the sequence holds true for x = n. Thus, by the inductive step, if the base step is true for x = 1 and the induction hypothesis x = n is also true, then the infinite sequence is valid for any positive integer x = n + 1 for n > = 1. To illustrate how induction works, a proof can be devised from a sequence with arbitrary positive integer n having property such that the sum of the first n even numbers is equal to n(n+1). By letting P denote this property, we can write this relationship as function P(n) and that P(n) = n (n+1). For these functions to be true, we must validate the base step, the

induction hypothesis, and the inductive step. Mathematical Induction To prove our sequence, the sum of the first n even numbers is equal to n(n+1), by mathematical induction, we must first state our proposition (that which is to be proved) in terms of property P, positive even integers n, and s the function of P(n) for n >=1: P(n) = 2+4+6...+2n = n(n+1): n > = 1 For this statement to be genuine, we must establish the cogency of the base step, by letting n be the smallest possible case (remember n>=1) which in this instance is 1 and substituting 1for n in our original function: P(n) = 2+4+6...+2n = n(n+1), if n = 1, then P(1) = 2(1) = 1(1+1) P(1) = 2 = 1(2) P(1) = 2 = 2 Hence, P(1) is true, and the base step is grounded. With the base step holding true, the original equation can be projected and assumed to be genuine in terms of a subsequent positive integer n such that: P(n) = n(n+1): n > = 1 3

From this assumption, an inductive hypothesis can be excogitated for this Mathematical Induction sequence: P(n+1) = 2+4+6...+2n+2(n+1) = (n+1){(n+1)+1} The next step is to prove the induction hypothesis by calculating the function P(n+1) in the original equation: P(n) = 2+4+6...+2n = n(n+1) By computing for P(n+1), the equation then becomes: P(n+1) = 2+4+6...+2n+2(n+1) = (n+1){(n+1)+1} From the original equation: P(n) = 2+4+6...+2n = n(n+1) the base step P(1) held true and, by inductive reasoning, P(n) was assumed to be valid. Therefore, by the substitution property of equality, we can rewrite P(n+1) as: P(n+1) = (2+4+6...+2n)+2(n+1) = (n+1){(n+1)+1} P(n+1) = P(n)+2(n+1) = (n+1)(n+2) P(n+1) = n(n+1)+2(n+1) = (n+1)(n+2) By using the distributive property of multiplication over addition and 4

algebraic computation, the equation can be reduced as to: P(n+1) = n+n+2n+2 = n+2n+n+2 P(n+1) = n+3n+2 = n+3n+2 Mathematical Induction 5

Consequently, P(n+1) is true, and, hence, P(n+2), P(n+3), and so on. This is in concordance with the Theorem of Mathematical Induction. Since the base, P(1), and subsequent integer n, P(n), are true and, by the induction step, the inductive hypothesis for P(n + 1) gradations coincided, the original sequence, P(n)= n(n + 1) thence is corroborated. Consequently, the original statement of arbitrary positive integer n having property such that the sum of the first n even numbers is equal to n(n+1) for all natural n >=1, is a valid sequence.